Examining Piil Pesenggiri Philosophy of Life Concept in the Context of Religious Moderation - Rimanto, Rimanto; Hermanto, Agus; Arsyad, Mufid; Rohmawati, Ari (Analisis: Jurnal Studi Keislaman, 2022)
Piil pesenggiri is a philosophy of life for Lampungnese people that is firmly held by Lampungnese people, as an ancestral heritage which can be said that Lampungnese people are predominantly Muslim, meaning that the philosophy of life then becomes closely related to the way of religion of Lampungnese people from time to time by maintaining a balance between local religious traditions themselves. This study is quite interesting to be discussed further, especially regarding the position of the piil pesenggiri philosophy of life in the moderate religious pattern of Lampungnese people. The method used is a descriptive method with a socio-philosophical approach, while drawing conclusions is by using a deductive thinking. The results of the study indicate that the values contained in the piil pesenggiri philosophy of life have a considerable influence on the Islamic style for Lampungnese people who are moderate and can maintain the values of balance between reason and morality on an ongoing basis.